(untitled) (Salam International Academic Journal, 2014)
Sayyid Jamal-ud-Din Afghan is one the personalities of the modern history who had great influence in the world. These influences were due to his tireless struggles and efforts against the tyranny and colonialism. Struggle against tyranny and colonialism is the most obvious characteristic of the life of Sayed Jamaluddin, no moment of his life has been without these struggles. His struggles were on the both intellectual and practical grounds. His intellectual struggle started from Afghanistan, continued to India and Turkey and reached its peak in Egypt. Even in Europe, he continued his struggles against tyranny and spent most of his time in stirring the East. In practical grounds, he utilized various means such as people to people contact, communicating with media organizations, forming political parties, educating and training personalities and leaders as alternative to rulers. Afghani’s inherent characteristics such as patience and persistence, courage and disinclination to worldly positions played great role in his struggles.